1976
DOI: 10.1007/bf01317830
|View full text |Cite
|
Sign up to set email alerts
|

Virus ?Tamdy? ? A new arbovirus, isolated in the Uzbec S.S.R. and Turkmen S.S.R. from ticksHyalomma asiaticum asiaticum Schulce et Schlottke, 1929, andHyalomma plumbeum plumbeum Panzer, 1796

Abstract: Eleven virus strains were isolated from ticks Hyalomma asiaticum asiaticum Schulce et Schlottke, 1929, and Hyalomma plumbeum plumbeum Panzer, 1796,collected in 1971-1974 in desert regions of the Uzbee S.S.R. and the Turkmen S.S.R. According to CF test the strains were closely related to each other and not antigenically connected with viruses from antigenic groups A, B, California, CHF-Congo, Bakau, Bunyamwera, Gajam, Kaisodi, Qalyub, Kemerovo, Quaranfil, Simbu, Turlock, Hughes, Uukuniemi, Tete and 21 ungrouped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…We therefore assign SAPV to the DGK genogroup. Thirdly, we have identified that three viral genome sequences detected in ticks from China (HTV1, TTV1, and WTV) 12 cluster phylogenetically with TDYV and BURV, which have previously been reported to be related genetically 38 , 49 ( Figures 1 and 2 ). Recognizing that HTV1, TTV1, and WTV are yet to be isolated and are represented only by genome sequences, we assign these putative viruses to the Tamdy genogroup.…”
Section: Discussionmentioning
confidence: 69%
“…We therefore assign SAPV to the DGK genogroup. Thirdly, we have identified that three viral genome sequences detected in ticks from China (HTV1, TTV1, and WTV) 12 cluster phylogenetically with TDYV and BURV, which have previously been reported to be related genetically 38 , 49 ( Figures 1 and 2 ). Recognizing that HTV1, TTV1, and WTV are yet to be isolated and are represented only by genome sequences, we assign these putative viruses to the Tamdy genogroup.…”
Section: Discussionmentioning
confidence: 69%
“…In this study, yet another nairovirus, TOV, was identified for the first time in the Arabian Peninsula. TOV was first found in H. asiaticum and H. plumbeum collected between 1971 and 1974 from deserts of Uzbekistan and Turkmenistan [ 35 ]. It has also been detected in other central Asian countries, such as Azerbaijan, Armenia and Kazakhstan [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The species Tamdy orthonairovirus (genus Orthonairovirus , family Nairoviridae ) includes 5 viruses: Tamdy virus (TAMV), Burana virus (BURV), Tǎchéng tick virus 1 (TcTV-1), Huángpí tick virus 1 (HpTV-1), and Wēnzhōu tick virus (WzTV) ( 1 ). TAMV and BURV were initially isolated from ticks in countries in central Asia ( 2 – 4 ), but little is known about their medical and veterinary importance. TcTV-1, HpTV-1, and WzTV were putative viruses identified by virome sequencing from ticks in China ( 5 ); however, their virologic properties and pathogenesis potential remain unclear.…”
mentioning
confidence: 99%